Light intensity modulates the accumulation of carbohydrates, antioxidant enzymes and production of iceberg lettuce under tropical conditions - Aires, Eduardo Santana [UNESP]; Aragão, Carlos Alberto; Dantas, Bárbara França; Rodrigues, João Domingos [UNESP]; Ono, Elizabeth Orika [UNESP] (MDPI, 2021)
High solar radiation in tropical regions can affect the development, physiology, and biochemistry of plants. Our aim with this research was to evaluate the biochemical responses and production of iceberg lettuce cultivars under environments with different shadings. An experiment under field conditions was installed in a 4 × 4 factorial scheme. Four cultivars of iceberg lettuce (Great Lakes, Winslow, Delicia, and Balsamo) and four environments with different shadings (three types of shading screens: red, ChromatiNet®, and black; and treatment under the full sun) were evaluated. Forty-five days after transplanting, the plants were harvested, and the biomass was weighed to obtain the fresh consumable part (FCP) and the biochemical parameters: total soluble sugar (TSS), reducing sugar (RS), and the activity of SOD, CAT, and POD. We found that shading modulates biochemical and productive responses of iceberg lettuce, and the main microclimatic factor related to these responses was solar radiation. We observed a negative correlation between RS and FCP. The solar radiation between 16 and 18 MJ·m−2·day−1, observed in the environments with a black screen and ChromatiNet®, promoted the highest activity of the SOD enzyme and average levels of TSS and RS, providing higher FCP of the cultivars Delícia and Balsamo in high temperatures period.
Keywords: Bolting; Lactuca sativa L; Physiology; Production; Shading; Sugars